1989
DOI: 10.1128/jvi.63.3.1455-1459.1989
|View full text |Cite
|
Sign up to set email alerts
|

Genetic recombination of human immunodeficiency virus

Abstract: We investigated genetic recombination of the human immunodeficiency virus (HIV) in a tissue culture system. A clonal cell line expressing a single integrated HIV provirus with a termination codon affecting pol gene expression was transfected with different defective mutants derived from an infectious molecular clone of HIV. Replication-competent viral particles were recovered, passaged, and plaque purified. Restriction analyses of the proviral DNA corresponding to several of these viruses indicated that their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(61 citation statements)
references
References 30 publications
3
58
0
Order By: Relevance
“…Genetic recombination contributes to the genetic variability of all species (Hannenhalli, Chappey, Koonin & Pevzner 1995; Jennings, Toebe, van Belkum & Wiser 1998; Vergunst, Jansen, Fransz, de Jong & Hooykaas 2000; Posada & Crandall 2001; Vogt 2004), including both RNA and DNA viruses (Galehouse & Duesberg 1978; Mocarski & Roizman 1981; Clavel, Hoggan, Willey, Strebel, Martin & Repaske 1989; Leppik et al 2007). For the WSSV, Marks et al (2004) reported a genome region prone to recombination located in ORF 14–15 and Dieu et al (2004), and Pradeep et al (2008) suggest that the differences in ORF 14–15 sequences are derived from deletions of different sizes and from different areas within those genome regions.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic recombination contributes to the genetic variability of all species (Hannenhalli, Chappey, Koonin & Pevzner 1995; Jennings, Toebe, van Belkum & Wiser 1998; Vergunst, Jansen, Fransz, de Jong & Hooykaas 2000; Posada & Crandall 2001; Vogt 2004), including both RNA and DNA viruses (Galehouse & Duesberg 1978; Mocarski & Roizman 1981; Clavel, Hoggan, Willey, Strebel, Martin & Repaske 1989; Leppik et al 2007). For the WSSV, Marks et al (2004) reported a genome region prone to recombination located in ORF 14–15 and Dieu et al (2004), and Pradeep et al (2008) suggest that the differences in ORF 14–15 sequences are derived from deletions of different sizes and from different areas within those genome regions.…”
Section: Discussionmentioning
confidence: 99%
“…Progeny can then become hybrid through different mechanisms, such as reassortment of segments when the parental genomes are fragmented [10], intra-molecular recombination when polymerases switch templates (in RNA viruses) [11], or homologous or non-homologous recombination (in both RNA and DNA viruses). Quantification of viral recombination in multicellular organisms has been attempted under two distinct experimental approaches: in vitro (in cell cultures) [12,13,14,15], and in vivo (in live hosts) [16,17,18]. The in vitro approach, which has so far been applied only to animal viruses, allows the establishment of the ''intrinsic'' recombination rate in experimentally co-infected cells in cell cultures [14,15,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, as discussed below, numerous experimental constraints have so far precluded an actual quantification of the baseline rate of recombination. First, many experimental designs have used extreme positive selection, where only recombinant genomes were viable (e.g., [13,20,21]). Other studies did not use complementation techniques but detected recombinants by PCR within infected hosts or tissues [18,22,23,24,25], which provides information on their presence but not on their frequency in the viral population.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals in a population differ from one another in their genetic sequences; when genetic material from two individuals is spliced through recombination to produce a new individual, whether this results from sexual reproduction or accidental recombination between two viral genomes present in the same host cell, the genetic sequence of the "offspring" involves adjacent regions derived from the two "parental" sequences, with a sharp changepoint in between. For HIV (the human immunodeficiency virus), this potential to recombine has been illustrated experimentally by Clavel et al (1989) and by Diaz et al (1995) and Salminen et al (1997) in natural infection in cases where the epidemiology is known in detail. It is of interest as another mechanism of generating genetic diversity in HIV infections and may be relevant to pathogenesis, viral escape of vaccines, and the development of drug resistance (see Diaz et al [1995] for discussion).…”
Section: Application: Assessing Genetic Recombinationmentioning
confidence: 99%